METAPHORIC COMPETENCE AND THE ACQUISITION OF FIGURATIVE VOCABULARY IN FOREIGN LANGUAGE LEARNING - Doiz, Aintzane; Elizari, Carmen (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Successful vocabulary teaching in the English as a foreign language classroom has to surmount many obstacles, such as the decrease in the rate of acquisition of new words by EFL students once a high level of proficiency is achieved, the students’ frustration at their inability to express their own thoughts adequately or plain boredom with the learning of lists of vocabulary items (MacArthur, 2010). In this article, we follow Danesi’s (2008) claim that the use of figurative language helps overcome some of these hurdles by providing the means to expand the learners’ vocabulary. The goal of this article is to highlight the importance of the role of metaphors in the acquisition of figurative vocabulary by learners of English in two contexts, an EFL classroom and a CLIL classroom. Firstly, we report on an experimental study where the consequences of developing conceptual metaphor awareness for figurative language learning in the EFL classroom are studied. Results show that, compared to the traditional translation-based approach, systematic presentation of the target figurative expressions on anger around the two conceptual metaphors they instantiate improves comprehension and spontaneous retention of the target vocabulary. Secondly, we implement the metaphor approach in the design of a lesson plan for a class of Philosophy and Citizenship where the medium of instruction is English (CLIL). We show that the metaphor awareness is instrumental in the accomplishment of two objectives: the learning of new figurative vocabulary in English and the understanding of the subject-matter targeted in the lesson plan. Resumen El éxito de la enseñanza del vocabulario en la clase de inglés como lengua extranjera está condicionado por factores como la disminución del índice de adquisición de palabras nuevas por parte de los estudiantes de inglés como lengua extranjera cuando alcanzan un nivel alto de competencia en la lengua, la frustración de los estudiantes por no poder expresar sus pensamientos de manera adecuada o el aburrimiento asociado a la memorización de listas de palabras nuevas (MacArthur, 2010). Siguiendo a Danesi (2008), defendemos que el uso del lenguaje figurativo puede ayudar a superar algunos de estos obstáculos al tiempo que contribuye a la ampliación del vocabulario. El objetivo de este artículo es destacar la importancia de las metáforas en la adquisición del lenguaje figurativo en dos contextos: una clase de lengua inglesa y una clase de AICLE. En primer lugar presentamos un estudio experimental en el que se consideran las consecuencias del uso de las metáforas para la adquisición de un grupo de expresiones figurativas sobre el enfado en una clase de inglés. El estudio muestra que el grupo en el que las expresiones fueron explicadas atendiendo a las metáforas conceptuales que las caracterizaban obtuvo mejores resultados en la comprensión y retención espontánea que el grupo en el que se utilizó el método tradicional basado en la traducción. A continuación implementamos el uso de la metáfora en el diseño de una lección para la asignatura de Philosophy and Citizenship en inglés (AICLE). Mostramos que este enfoque consigue dos objetivos: ampliar el vocabulario figurativo del alumnado y mejorar la comprensión del contenido asociado a la unidad docente de la asignatura.